2018
DOI: 10.3390/ijms19102989
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of a Homodimeric Laccase from Cerrena unicolor BBP6 by Random Mutagenesis and In Vivo Assembly

Abstract: Laccases have great potential for industrial applications due to their green catalytic properties and broad substrate specificities, and various studies have attempted to improve the catalytic performance of these enzymes. Here, to the best of our knowledge, we firstly report the directed evolution of a homodimeric laccase from Cerrena unicolor BBP6 fused with α-factor prepro-leader that was engineered through random mutagenesis followed by in vivo assembly in Saccharomyces cerevisiae. Three evolved fusion var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…This can be induced through genetic means, such as synthetic biology, targeted gene editing, or genetic engineering. For example, Zhang et al (2018) used random mutagenesis and site-directed mutagenesis to increase the production of the degrading enzyme, laccase, by 31to 37-fold in the white-rot fungus Cerrena unicolor BBP6. Similar approaches could be used to increase the biocatalytic activities of microalgal laccases.…”
Section: Algal Biodegradation Of Emerging Contaminantsmentioning
confidence: 99%
“…This can be induced through genetic means, such as synthetic biology, targeted gene editing, or genetic engineering. For example, Zhang et al (2018) used random mutagenesis and site-directed mutagenesis to increase the production of the degrading enzyme, laccase, by 31to 37-fold in the white-rot fungus Cerrena unicolor BBP6. Similar approaches could be used to increase the biocatalytic activities of microalgal laccases.…”
Section: Algal Biodegradation Of Emerging Contaminantsmentioning
confidence: 99%
“…Firstly, the conditions of the growth media can be optimized to enhance the secretion, activity and stability of native laccases, for instance, Otto et al (2010) found increased laccase production in microalgae was achieved through the simple addition of copper sulphate. Secondly, the catalytic performance of the native enzymes can be increased by random mutagenesis and/or site-directed mutagenesis (Zhang et al 2018). Finally, exogeneous enzymes, such as fungal enzymes with high biodegradation capacity, can be recombinantly expressed in microalgae.…”
Section: Algae Based Processmentioning
confidence: 99%
“…Heterologous expression of genes encoding the ligninolytic enzymes has been one of the strategies to solve these problems (Fernández-Fueyo et al, 2014). To date, manymnp and laccase genes from different WRF, e.g.,Ganoderma lucidum (Xu et al, 2017), Irpex lacteus (Chen et al, 2015), Phanerochaete chrysosporium (De et al, 2020),Pleurotus eryngii (Sato et al, 2017), and Cerrena unicolor (Zhang et al, 2018c), have been cloned and expressed in a various species of hosts. Due to its fast growth, clear genetic background, and high biosafety, yeast has been frequently used as the host strain for the expression of genes encoding ligninolytic enzymes (Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, a native MnP (MnP-BBP6; Zhang et al, 2018a) and a laccase (LacA; Zhang et al, 2018b) were purified from the extracellular broth of C. unicolor BBP6 and applied to both denim bleaching and dye decolorization. Subsequently, a mnp gene (mnp3-BBP6 ; Zhang et al, 2020) and a laccase gene (lacA ; Zhang et al, 2018c) were cloned from C. unicolor BBP6 and expressed in yeast, respectively. The results revealed that the synergism was formed between laccase and MnP in the process of denim bleaching by purified LacA and MnP-BBP6 (Zhang et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%